Multi‐level LINC transmitter with non‐isolated power combiner. Issue 25 (1st December 2013) - Hur, J.; Kim, H.; Lee, O.; Woo, S.; Kim, K.; Kim, W.; Lee, C.‐H.; Lim, K.; Laskar, J.
Abstract : By using a non‐isolated power combiner, the overall power efficiency can be improved by reducing the wasted power at the combined out‐phased signal. To further improve the efficiency of the low‐power mode, a multi‐power mode out‐phasing power amplifier (PA) is proposed with load modulation by switches. Compared with the conventional linear amplification using nonlinear component (LINC) transmitter, the proposed multi‐level LINC improves the power‐added‐efficiency more than 40% for a 7 dB peak‐to‐average power ratio orthogonal frequency division multiplexing signal. To the authors' knowledge, the proposed LINC PA is the first multi‐level LINC PA without multiple power supplies.